2016
DOI: 10.3928/01477447-20160315-05
|View full text |Cite
|
Sign up to set email alerts
|

The Boxer's Fracture: Splint Immobilization Is Not Necessary

Abstract: Fractures of the fifth metacarpal neck, or boxer's fractures, are common, particularly among young men. Because of the high frequency of this injury, there is a considerable range of treatment options. The purpose of this systematic review was to determine whether reduction and splint or cast immobilization is necessary for fractures of the fifth metacarpal neck. The authors conducted a systematic review of all published studies that randomized these fractures to cast immobilization vs treatment with soft wrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 25 publications
1
35
1
Order By: Relevance
“…Previous studies and literature were used to build this project of updating our practice to match current evidence-based practice and save healthcare costs. 9,10,1316…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies and literature were used to build this project of updating our practice to match current evidence-based practice and save healthcare costs. 9,10,1316…”
Section: Methodsmentioning
confidence: 99%
“…5,6 The concern is that residual angulation at the fifth metacarpal may leave patients with discomfort and aesthetic complaints. 7,8 A recent review by Dunn et al 9 debunked this theory; the authors contend that given acceptable short- and long-term outcomes, it is reasonable to pursue nonoperative treatment for up to 70 degrees 10 apex dorsal angulation without a rotational deformity. These authors also demonstrated that the evidence suggests a soft wrap with buddy taping the fourth and fifth digit without reduction yields equivalent results to closed reduction and splint treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clinical evidence from young active duty military personnel suggests that casting in extension with appropriate 3-point molding provides equivalent functional and radiographic outcomes, with faster application and better tolerability [10,11]. Although a recent review suggests that a simple soft wrap may be sufficient treatment for the ubiquitous metacarpal neck fracture, [12] the included literature does not specifically address athletes.…”
Section: Nonoperative Treatmentmentioning
confidence: 99%
“…2 In more recent randomized controlled trials and meta-analyses, functional outcomes were similar. 9,10,14 Because discomfort, hand function, and ability to work may be considered variably per patient-clinician interaction, the current data are insufficient to provide consensus for the optimal management of patients with boxer's fractures. 2,9 Editor's Capsule Summary What is already known on this topic Plaster immobilization is a standard emergency department (ED) treatment for patients with a fifth metacarpal (boxer's) fracture, but buddy taping is less studied.…”
Section: Introduction Backgroundmentioning
confidence: 99%